2008
DOI: 10.1177/1721727x0800600307
|View full text |Cite
|
Sign up to set email alerts
|

Lack of HCV Replication during the Course of HCV-Associated Arthritis

Abstract: Viral replication was evaluated by PCR in the serum of 25 subjects with lICV-associated arthritis. Active replication resulted in 16 cases, only 10 of which presenting hypertransaminasemia. A significant correlation appeared between serum Rheumatoid Factor concentrations and viral replication only in 7 patients with hypertransaminasemia. These data suggest that the onset of arthritis in this infection is due to an autoimmune mechanism, not linked to the HCV replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For example, the question of a connection between vaccination and autism is surrounded by controversy. In addition, several studies showing elevated brain-specific antibodies in autism support an autoimmune mechanism (22)(23)(24)(25). However, recently it has been reported that vaccines, as well as autoimmunity do not seem to be the cause of autism.…”
mentioning
confidence: 99%
“…For example, the question of a connection between vaccination and autism is surrounded by controversy. In addition, several studies showing elevated brain-specific antibodies in autism support an autoimmune mechanism (22)(23)(24)(25). However, recently it has been reported that vaccines, as well as autoimmunity do not seem to be the cause of autism.…”
mentioning
confidence: 99%
“…Mast cell producing cytokines/chemokines can substantially enhance T cell recruitment to local infection demonstrating that they are not only important in IgE-associatcd disorders, but also contribute to the host defence against bacteria (36)(37)(38)(39)(40)(41). Mast cells have diverse potential contribution during innate and acquired immunity and in other biological responses (42)(43)(44)(45). These findings suggest that mast cells may have a much more versatile role than previously suspected.…”
Section: Discussionmentioning
confidence: 90%